Libraries Driving Education for Sustainable Development (IFLA Publications, 2025)
Libraries, especially green and sustainable libraries, deserve prominent recognition as learning institutions and active driving partners for Education for Sustainable Development and which support their governments’ sustainability efforts. In line with the Berlin Declaration on ESD and the UNESCO program, the book focuses on innovative approaches and informal education projects, created and provided by green and sustainable libraries.